Health Status and Quality of Life in Depok Slum Communities through Stunting Prevention - Siregar, Tatiana; Ritanti, Ritanti; Permatasari, Indah; Utari, Dyah; Ratnawati, Diah (Poltekkes Kemenkes Surakarta, 2025)
Background: There are 11 slum areas in Depok City. Slums are correlated with populations that are easily exposed to diseases and have limited economic capabilities, resulting in the lack of hygiene and healthy living behaviors (PHBS), including adequate nutritional needs. This living condition poses a risk of reducing the quality of life of the residents. This research aims to determine the correlation between health status and quality of life to prevent stunting among residents in slum areas of Depok City. Method: This study employed a quantitative cross-sectional research design. A total of 160 respondents were selected using a non-probability quota sampling technique from a population of 400 heads of households across four identified urban slum areas. Data were collected using the World Health Organization Quality of Life–BREF (WHOQOL-BREF) instrument and were analyzed using Chi-Square test. Results: All dimensions of the health status variable namely physical environment, social conditions, economic conditions, mental health, healthcare support, and family support demonstrated a significant relationship with each dimension of quality of life, including physical health, psychological health, social relationships, and environmental well-being (all dimensions p < 0.05). All independent variables showed p-values < 0.05 based on Chi-Square analysis. Conclusion: Given the proven significant influence of health status on the quality of life of residents in slum areas, it is hoped that the Depok City government will undertake development efforts to improve these slum areas so that the Human Development Index (HDI) of Depok City can be achieved, thereby fulfilling the Sustainable Development Goals (SDGs).